Platelet phosphatidylserine exposure and microparticle production as health bioindicators in marine mammals - Felipo-Benavent, Mar; Valls, Mónica; Monteiro, Maria Céu; Jávega, Beatriz; García-Párraga, Daniel; Rubio-Guerri, Consuelo; Martínez-Romero, Alicia; O’Connor, José-Enrique (Frontiers in Veterinary Science, 2024)
In human medicine, several pathologies as decompression sickness, thrombocytopenia or rheumatoid arthritis have been proved to correlate with an alteration in cellular microparticles (MP) formation, such as platelet microparticles (PMP). In marine mammals, similar disorders may be directly related to anthropogenic threats or sickness and blood PMP levels may be affected. We propose that detecting platelet phosphatidylserine (PS) exposure and PMP formation can serve as a valuable diagnostic and monitoring tool for these pathologies in marine mammals. Our group has adapted a methodology for evaluating real time PS exposure and PMP formation in this taxonomic group. This method employed for the first time in species like bottlenose dolphins, beluga whales, walruses and California sea lions, represents a novel and valuable tool to both clinical assessment and further research on platelet function.